Design of fuzzy logic system for cognitive radio networks for efficient spectrum decision and channel assignment - Suneetha, Ch; Srinivasa Rao, S; S. Ramesh, K (International Journal of Engineering and Technology, 2018)
Wireless sensor networks (WSNs) are becoming highly preferable for various day to day applications. Cognitive radio (CR) is a paradigm that can deploy IPV6, which has built-in auto configuration features along with large 128-bit address space for efficient spectrum allocation by considering all possible QOS parameters. An efficient spectrum decision has been developed based on fuzzy for secondary users channel assignment. The parameter such as Signal strength, node velocity and distance between PU and SU for unused available BW IPV6 header has been identified for information such as text, voice or video to be forwarded by the Secondary users with efficient spectrum allocation. The spectrum decision and channel assignment for secondary users has been simulated to obtain satisfactory resultsÂ Â